Prognosis models of nitrates and orthophosphates content in surface waters - Mitryasova, Olena P.; Shybanova, Alla M.; Dzhumelia, Elvira A. (Kyiv National University of Construction and Architecture, 2022)
The dynamics of hydrochemical parameters such as nitrates, and orthophosphates of surface waters were analyzed. Based on the analysis of wide temporal monitoring data, of prognosis nitrates and orthophosphates of the surface waters were carried out.The purpose is an assessment of the state of the surface water by nitrates and orthophosphates hydrochemical parameters and their regression analysis.The object of research – was to determine nitrates and orthophosphates indicators of the river water state during 12 years.The regression analysis method using the Windows Excel CurveExpert software was used to determine the empirical dependencies and search for connections.Against the background of high regulation of the Inhul river basin (the presence of 770 ponds and an irrigation system on 33 hectares, water use is carried out by more than 20 enterprises) showed the periodic nature of changes in hydrochemical parameters. Based on the obtained functions, prognoses to 2030 on annual averages were developed. The study is the basis for determining the mathematical model of natural fluctuations of the research indicators. Regression analysis allows obtaining a sinusoidal dependence on the orthophosphates content, which demonstrates 13 years fluctuation (R = 0.90). We have an 11-year sinusoidal wave with a period of 10 years and fairly high representativeness (R = 0.85) for nitrate content. The determined sinusoidal dependences of the integrated indicators of water quality allowed determining the average time of fluctuations concerning the processes of self-organization of river waters, which is about 11 years, and confirms the theory of "waves of life". The surface waters of the river are capable of self-renewal and their hydrochemical status has not yet reached a critical point, after which irreversible changes in the river ecosystem may occur.